Development and optimization of a novel automated loop method for production of [11C]nicotine. (October 2018) - Ghosh, Arijit; Woolum, Karen; Knopp, Michael V.; Kumar, Krishan
Abstract: A novel, rapid, and automated loop method for the synthesis of [ 11 C]nicotine was developed and optimized. The method involves, a reaction of the precursor, (+ ) nornicotine or (-) nornicotine, with a gas-phase produced [ 11 C]CH3 I in an 800 µL loop at 75 °C for 5 min followed by a semi-preparatory Reversed-Phase High-Performance Liquid Chromatography (RP-HPLC) purification. The optimized synthesis and purification process was complete in < 30 min and produced [ 11 C]nicotine with > 99.9% Radiochemical Purity (RCP), no [ 11 C]CH3 I, no (+ ) nornicotine, 105 mCi/µmole specific activity, 7.0 – 7.2 pH, and 16.6% ethanol. The current method can be optimized, to reduce the ethanol content (<10%), and can be translated to a cGMP production of [ 11 C]nicotine for human clinical trials. Highlights: A novel, rapid, and automated loop method for synthesis of [ 11 C]nicotine is reported. The reaction involves gas-phase produced 11CH3I and base form of (±) nornicotine or (-) nornicotine. The optimized process produced [ 11 C]nicotine with > 99.9% Radio Chemical Purity (RCP), no [ 11 C]CH3 I, no (±) nornicotine. An analytical HPLC method with a short run time was developed. The automated loop method for synthesis can be translated for GMP production of [ 11 C]nicotine for human clinical trials.